A universal strategy for the incorporation of internal standards into SERS substrates to improve the reproducibility of Raman signals. Issue 23 (26th October 2021) - Lin, Bingyong; Yao, Yuanyuan; Wang, Yueliang; Kannan, Palanisamy; Chen, Lifen; Guo, Longhua
Abstract : This scheme shows the comparison of Au NBP SERS substrates in the presence and absence of ISs. The reproducibility of the signals of the IS-modified SERS substrate was improved significantly. Abstract : The uneven distribution of metal nanoparticles is a vital influencing factor in the poor uniformity of surface-enhanced Raman scattering (SERS) substrates, which is a challenge in SERS quantitative analysis. Recent reports showed that the reproducibility of a nonuniform SERS substrate can be effectively improved by the use of an internal standard (IS). However, most of these approaches require the investment of time for precise regulation, and those approaches based on the addition of an IS are specific to a certain substrate. In this work, we proposed a simple, rapid and universal method to incorporate an IS into a SERS substrate for improving the reproducibility of Raman signals based on the systematic evaluation of the influencing factors of the competitive adsorption between the IS and the target analytes. Following the proposed pressure drop-coating (PDC) method, an IS-modified gold nanobipyramids (Au NBPs)/anodic aluminum oxide (AAO) SERS substrate was fabricated within 1 min, showing high reproducibility of Raman signals. In addition, the IS-modified Au NBPs/AAO SERS substrate was successfully applied to analyze thiram in freshly squeezed apple juice and the result showed a stable Raman signal with a relative standard deviation of less than 6.00%. What is more, three different commercial SERS chips were modified with an IS molecule using the PDC method. Compared to the traditional SERS chips, the Raman signal reproducibility of the functionalized SERS chips was improved significantly. Since the addition of an IS is not based on a certain substrate, the proposed approach could be useful for all the researchers working in the field of SERS.